The Effect of Responsiveness and Location on Customer Satisfaction on Service Users of Yevame Laundry Medan - T Teviana (Outline Publisher, 2022)
This study aims to determine the effect of Responsiveness and Location on Customer Satisfaction of Yevame Laundry Service Users in Medan. This study used a quantitative method with a sampling technique using a purposive sampling technique, with a total sample of 97 people who had used the services of Yevame Laundry Medan. The data collection technique in this study was carried out by distributing questionnaires whose measurements were using a Likert scale and statistically processed using multiple linear regression analysis and hypothesis testing with the F-test, T-test and Coefficient of Determination, previously the data had been tested using the validity test. reliability and classical assumption test. Data processing uses the SPSS 18.00 program for windows. Partially responsiveness and location have a positive and significant effect on customer satisfaction for users of yevame laundry Medan. Based on the results of the study, it shows that responsiveness and location variables simultaneously influence customer satisfaction. This can be seen from the calculated F value > Ftable (200.632 > 3.09) and a significant value of 0.000 <0.05. The coefficient of determination test shows a value of 0.806 which means that responsiveness and location affect customer satisfaction by 80.6% while the rest is influenced by other variables.